1989
DOI: 10.1021/bk-1989-0388.ch002
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Chiral Flavor and Aroma Compounds in Plants and Microorganisms

Abstract: Capillary gas chromatographic determination of optical purities, investigation of the conversion of potential precursors, and characterization of enzymes catalyzing these reactions were applied to study the biogenesis of chiral volatiles in plants and microorganisms. Major pineapple constituents are present as mixtures of enantiomers. Reductions, chain elongation, and hydration were shown to be involved in the biosynthesis of hydroxy acid esters and lactones. Reduction of methyl ketones and subsequent enantios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…Additionally, two diastereomers of methyl 3-acetoxy-2-methylbutanoate were identified as discriminative volatiles formed during post-harvest storage of pineapple fruits. These findings are in good agreement with our previously published results [13,15] and other studies on the post-harvest flavour genesis of pineapple fruit [11,28]. Sea-freighted pineapples stored for post-harvest flavour genesis (GR 25 dah) were additionally characterised by elevated concentrations of hexanal (see Table 2), exhibiting green and grassy notes [23].…”
Section: Hs-spme-gc-ms Profiling Analysissupporting
confidence: 92%
“…Additionally, two diastereomers of methyl 3-acetoxy-2-methylbutanoate were identified as discriminative volatiles formed during post-harvest storage of pineapple fruits. These findings are in good agreement with our previously published results [13,15] and other studies on the post-harvest flavour genesis of pineapple fruit [11,28]. Sea-freighted pineapples stored for post-harvest flavour genesis (GR 25 dah) were additionally characterised by elevated concentrations of hexanal (see Table 2), exhibiting green and grassy notes [23].…”
Section: Hs-spme-gc-ms Profiling Analysissupporting
confidence: 92%
“…In ripened pineapples, ethyl acetate (33.5%), threo-butane-2,3-diol diacetate (13.0%), and 3-hydroxy-2-butanone (8.7 %) were the major constituents. Engel et al (1989) demonstrated that the concentrations of hydroxy and acetoxy acid esters increased during pineapple ripening. 3-Hydroxy-2-butanone has been reported as a main volatile constituent in a vacuum steam distillate from canned pineapple juice The descriptive analysis was done with an aqueous solution of each compound at the level of 1-10 ppm.…”
Section: Resultsmentioning
confidence: 98%
“…Alpha) ( 17), but this is the first time these compounds are identified in pocket melon. Engel et al (22) and Umano (24) have shown that the concentrations of hydroxy and acetoxy acid esters increased during pineapple ripening. Nevertheless, according to Wyllie and Leach (8), 2,3butanediol diacetate has a sweet odor and appears to have high odor threshold and, therefore, would not be expected to have a significant role in the aroma of melon (cv.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, the levels of acetoxy and hydroxy esters were particularly predominant in skin. Although these compounds are generally found in tropical fruits such as passion fruit, pineapple, and mango ( ), 2,3-butanediol diacetate ( 28 , 32 ) and its precursor 3-acetoxy-2-butanol ( 36 , 37 ) have been previously identified in Japanese melon (cv. Golden Crispy) () and in C. melo var.…”
Section: Resultsmentioning
confidence: 99%